2008
DOI: 10.1007/bf03086130
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and misdiagnosis of chronic heart failure in nursing home residents: the role of B-type natriuretic peptides

Abstract: Background/objectives. Without knowing the exact CHF prevalence, chronic heart failure (CHF) occurs frequently in elderly people both inside and outside nursing homes. For a diagnosis we have to rely on physical examination and additional tests. We therefore run the risk of missing CHF diagnoses or of diagnosing CHF when we should not. Natriuretic peptide assays have emerged as a diagnostic test but their use in nursing home residents is limited. We examined the number of misdiagnoses, the CHF prevalence and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
37
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 22 publications
6
37
3
Order By: Relevance
“…The high percentage of care home residents with previously unknown CHF (69% of all residents with CHF) proved in good agreement with the encountered 62% of previously unknown CHF in the afore-mentioned study in The Netherlands (2). Masking of CHF symptoms by co-morbidity, mild symptoms, and also unfamiliarity of general practitioners with the diagnostic value of the BNP may explain the underestimation.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The high percentage of care home residents with previously unknown CHF (69% of all residents with CHF) proved in good agreement with the encountered 62% of previously unknown CHF in the afore-mentioned study in The Netherlands (2). Masking of CHF symptoms by co-morbidity, mild symptoms, and also unfamiliarity of general practitioners with the diagnostic value of the BNP may explain the underestimation.…”
Section: Discussionsupporting
confidence: 83%
“…However, BNP is less often used in care homes, because co-morbidity, a widespread characteristic of its residents, complicates the interpretation of the BNP outcomes (2). For example, misinterpretation may be caused by renal dysfunction, acute coronary syndrome, pulmonary embolism, obesity, age, gender and critical illness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data in HF patients with diabetes further establish the important role of these natriuretic peptides in (suspected) HF. 29 n references…”
Section: Discussionmentioning
confidence: 99%
“…Our findings of detecting occult CHF is consistent with others' findings when comparing the detection sensitivity of a biomarker with physical examination. 13 Physical examination is not only inadequate for the detection of volume overload, but it is also unable to accurately detect volume depletion. 14 Some previous studies have questioned the validity of BNP utilization in ESRD [15][16][17] and found ''no correlation between the plasma levels of BNP and body weight changes during HD.''…”
Section: Discussionmentioning
confidence: 99%